Decoding Ethereum's Brand Personality via YouTube Content Analysis - Janfry Sihite; Arissetyanto Nugroho; Zulkifli Zulkifli; Yuli Harwani; Darmansyah Darmansyah (Penerbit Goodwood, 2026)
Purpose: This study examines Ethereum’s brand identity as a decentralized blockchain platform, focusing on how its narrative is co-created and negotiated within the YouTube ecosystem and its implications for market positioning and investor behavior.Research Methodology: A quantitative content analysis and text mining approach was applied to 355 English-language YouTube video descriptions using WordStat software, Brand Personality, sentiment analysis, Term Frequency–Inverse Document Frequency (TF-IDF), Named-Entity Recognition (NER), and hierarchical cluster analysis.Results: The findings show that competence is the dominant brand personality trait (52.48%), followed by excitement (28.37%). Sentiment analysis reveals balanced polarity, with 50.37% negative and 49.63% positive sentiments. Ethereum’s brand narrative is strongly shaped by financial and institutional adoption discussions.Conclusions: Ethereum’s co-created brand identity reflects technological competence and speculative excitement. Without centralized marketing control, YouTube intermediaries influence brand narratives by transforming technical blockchain concepts into financial investment narratives.Limitations: The study focuses only on textual metadata from English-language YouTube videos and does not include visual content or cross-cultural perspectives.Contributions: This study extends digital marketing and decentralized finance research by applying brand personality theory to Decentralized Autonomous Organizations (DAOs) and digital assets.